Disparity Map Algorithm Based On Edge Preserving Filter For Stereo Video Processing - Hamzah, Rostam Affendi; Abd Gani, Shamsul Fakhar; Hamid, Mohd Saad; Kadmin, Ahmad Fauzan; Salam, Saifullah (Penerbit Universiti, UTeM, 2018)
This paper proposes a new local-based stereo matching algorithm for stereo video processing. Fundamentally, the Sum of Absolute Differences (SAD) algorithm produces an accurate results on the stereo video processing for the textured regions. However, this algorithm sensitives to low texture and radiometric distortions (i.e., contrast or brightness). To overcome these problems, the proposed algorithm utilizes edgepreserving filter which is known as Bilateral Filter (BF). The BF algorithm reduces noise and sharpen the images. Additionally, BF works fine on the low or plain texture areas. The proposed algorithm produces an accurate results and performs much better compared to some established algorithms on the standard benchmarking results of the Middlebury and KITTI dataset.